(3WHbGJ GdTGaYjIs - (3CHh HcQ Hf CMeO Hf eMeO Hf YeQ GdCSOj GdTgHj GdOeTbqj, Jbqj GdOjf , (B851 (3g`s
(3ChdgG (B:s
(3GdMeO ddg dGPi QaY KOQ GdYdeGA hLYdge HefRdI GdfLhe ai GdSeGA s
(3BNQgG (B:s
(3Jc cJGH GdWHbGJ hGdMeO ddg QH GdYGdejf hGdUdGI hGdSdGe Ydi CTQa GdeQSdjf s
(3GfXQ HbjI fSN gPG GdcJGH ai GdbSe GdChd ef gPG GdagQSJ HQbe (B312s
(3QJHg Ydi JSY hYTQjf WHbis
(3hQJH cd WHbI Ydi NQha GdeYLes
(3fSNI KGdKI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B61 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B57s
Keywords: (3GdJGQjNs